A estética do cinema nazista na produção dos sentidos na comunicação política no Brasil - Jimenes, Roberto (2023)
There are many studies that address Nazi Cinema and this had a fundamental role in Hitler's plans, with cinema being the main means of communication used at the time. Several were the cinematographic languages used, however, studying Nazi cinema against the study of visual culture, it is possible to draw a parallel between some points: such as the relationships between visibility (what cinema provides), visuality (the new cinema: entertainment x politics) and power (Nazism), which transform the universe of symbolic understanding among the German population. Is it possible that, when analyzing the images of this cinema, we cannot propose a counter-visuality, if we consider its aesthetics associated with a new analysis of the production of meanings. The implications regarding these visual experiences in a society increasingly centered on the meaning of the gaze, and its repercussions even today in the universe of political and governmental communication in Brazil.